Supporting first-year student academic literacy development and emotional well-being through a pedagogy of care in South African writing centres - Namakula, Halima (Critical Studies in Teaching and Learning, 2024)
Writing centres are often described as supportive, non-judgemental spaces that aid student academic literacy development, promote well-being, and encourage a sense of belonging and self-assurance. This paper explores how writing centre pedagogy intersects with care principles to support student academic literacy at a South African university in the Gauteng Province. Qualitative methods, such as individual and focus group interviews, were used to collect data from students and peer tutors to understand their perspectives on writing centre practices. Findings indicate that the writing centre is a familial space where friendships and emotional support coexist with academic literacy development. Additionally, peer tutors help students feel safe in potentially alienating and unfamiliar spaces, especially for first-year students. This paper emphasizes the importance of environments that support academic growth and community, suggesting that care-infused pedagogy in writing centres can empower students and enhance academic success.